Aloe vera: A promising natural herbal supplement for enhancing growth, physiology, antioxidant activity and immunity in Catla catla - Zeeshan Yousaf; Syed Makhdoom Hussain; Shafaqat Ali; Dariusz Kucharczyk; Joanna Nowosad; Konrad Turkowski; Bilal Ahamad Paray; Adan Naeem (Aquaculture Reports)
Aloe barbadensis (L.) Mill. (A. vera) is a well-recognized herbal supplement in aquaculture feeds, known for its ability to promote overall health. This research demonstrates the beneficial effects of dietary A. vera supplementation on growth, carcass composition, digestibility, hematology, antioxidant status, and immune parameters in Catla catla. A total of 270 C. catla fish (average weight: 6.50 ± 0.03 g) were uniformly assigned into six treatment groups, each replicated in triplicate. The groups fed diets containing equal amounts of canola meal and varying levels of A. vera supplementation (0 %, 1 %, 2 %, 3 %, 4 %, and 5 %). The fish were fed at a rate equivalent to 5 % of their live wet body weight. The findings determined that fish fed an A. vera supplemented diet exhibited significant improvements in all parameters. Supplementation with 3 % A. vera resulted in a significant (p < 0.05) increase in weight gain (%) and an improved feed conversion ratio. Moreover, highest digestibility coefficients for crude protein, gross energy, and crude fat, as well as optimal carcass values for fat and crude protein content, were observed at 3 % A. vera supplementation level. Hematological analysis revealed significant differences (p < 0.05) in white blood cells, red blood cells, platelets, and hemoglobin levels in fish fed at 3 % A. vera diet. Notably, antioxidant activities and immune parameters also showed maximum output at the 3 % A. vera supplementation level.